Synthesis and characterization of stable bis(methoxo)platinum(IV) complexes. A facile synthesis via fluorenylidene-philic interactions - Lee, YA; Jung, OS (CHEMICAL SOC JAPAN, 2002)
Stable mono- and bis(methoxo)platinum(IV) species via the oxidation of Pt-II to Pt-IV have been prepared and characterized. The reaction of [Pt-II(fpd)(dpda)] (fpd = 9-fluorenylidenepropanedioate; dpda = 2,2-dimethyl-1,3-propanediamine) with hydrogen peroxide in methanol at room temperature affords [Pt-IV(OH)(OCH3)(fpd)(dpda)], and further reaction at boiling methanol produces a bis(methoxo)platinum(IV) compound, [Pt-IV(OCH3)2(fpd)(dpda)]. The bis(methoxo)platinum(IV) compound can be prepared by the direct reaction of [Pt-II(fpd)(dpda)] with hydrogen peroxide in boiling methanol or by the simple stirring of [Pt-IV(OH)2(fpd)(dpda)] in boiling methanol. The crystal structures of [Pt-II(fpd)(dpda)].2(CH3)(2)NCHO (Pna2(1), a = 10.125(2) Angstrom, b = 26.141(4) Angstrom, c = 10.845(6) Angstrom, V = 2870(2) Angstrom(3), Z = 4, R = 0.0370), [Pt-IV(OH)(2)(fpd)(dpda)].3C(2)H(5)OH (P2(1)/a, a = 10.312(2) Angstrom, b = 22.044(5) Angstrom, c = 14.225(3) Angstrom, beta = 110.25(2)degrees, V = 3034(1) Angstrom(3), Z = 4, R = 0.0572), and [Pt-IV(OCH3)(2)(fpd)(dpda)].1.5CH(3)OH.0.5C(2)H(5)OH.0.5H(2)O (P(1) over bar, a = 13.333(2) Angstrom, b = 15.386(3) Angstrom, c = 18.446(5) Angstrom, alpha = 66.80(2), beta = 69.06(2)degrees, gamma = 68.84(1), V = 3140(1) Angstrom(3), Z = 2, R = 0.0437) have been solved and refined. For [Pt-IV(OCH3)(2)(fpd)(dpda)], the 9-fluorenylidene moiety of fpd ligand snugly interacts with the methoxo group (C(22)...C(9), 3.34 Angstrom; C(22)-H...C(9), 2.65 Angstrom). The mono- and bis(methoxo)platinum(IV) compounds are stable even in solution.
Keywords: PLATINUM(II) COMPLEXES; OXIDATIVE ADDITION; BONDING MODE; LIGANDS; COORDINATION